AN OBSERVATION ON CERTAIN MISTAKES MADE IN THE RESTORATION WORK OF HISTORICAL BUILDINGS AND THE UNDERLYING REASONS IN LIGHT OF HALIME HATUN CUPOLA - BAŞAK, Oktay (SSD Journal, 2018)
Anatolia that accommodates numerous works of art and monuments belonging to diverse civilizations is among the few geographies in the world in terms of great amount and diversity of historical buildings. Although significant work has been done to preserve and carry into the future this wealth, unfortunately the desired level has not been attained yet. Although the repair and maintenance of historical buildings is a work requiring great diligence and expertise, sometimes irreparable destructions could be caused in historical buildings and monuments due to the fact that a significant part of the society is not sensitive towards immovable cultural property and the awareness for preserving them has not been instilled in a great part of the society yet as well as the ignorance of preserving the traditional fabric. Since historical buildings as part of immovable cultural property are historical documents, it is a necessity to perform interventions on them as little as possible unless really necessary, and to preserve the buildings through conservation and consolidation methods rather than renovation in order to prolong their life and prevent any destruction that may happen in the future. As in many other countries, interventions could be made in Turkey as well under the name of restoration to remedy certain damages caused by nature and humans. However, there also may be some practices that unknowingly expedite such destruction because necessary interventions are not made on time or as result of wrong practices as in the case of Halime Hatun Cupola.